Clinical, biochemical and molecular characterization of Korean patients with mucolipidosis II/III and successful prenatal diagnosis. Issue 1 (December 2017) - Yang, Mina; Cho, Sung; Park, Hyung-Doo; Choi, Rihwa; Kim, Young-Eun; Kim, Jinsup; Lee, Soo-Youn; Ki, Chang-Seok; Kim, Jong-Won; Sohn, Young; Song, Junghan; Jin, Dong-Kyu
Abstract Background Mucolipidosis types II and III (ML II/III) are autosomal recessive disorders caused by a deficiency in the lysosomal enzyme N-acetylglucosamine-1-phosphotransferase. We investigated the molecular genetic characteristics of theGNPTAB gene, which codes for the alpha/beta subunits of a phosphotransferase, in Korean ML II/III patients. We included prenatal tests and evaluated the spectrum of mutations in East Asian populations with ML II/III through a literature review. Methods Seven patients from six families were enrolled in the study including two prenatal tests using chorionic villi samples. A diagnosis of ML II/III was made based on clinical findings and increases in serum lysosomal enzyme levels. PCR and direct sequencing were performed to identifyGNPTAB mutations. Results We found 14 mutant alleles including seven known mutations of c.2189delT (p.Leu730fs*7), c.1090C > T (p.Arg364*), c.2681G > A (p.Trp894*), c.3565C > T (p.Arg1189*), c.310C > T (p.Gln104*), c.1071G > A (p.Trp357*) and c.2574_2575delGA (p.Asn859Glnfs*2). Four were novel variants of unknown significance: c.992A > G (p.Tyr331Cys), c.2666 T > A (p.Leu889*), c.637-6 T > G (p.Thr213Phefs*11), and c.471_472delTT (p.Tyr158Serfs*8). Family studies revealed the probands to be compound heterozygotes. The fetuses carried the sameGNPTAB mutations as the mucolipidosis II/III probands in the prenatal diagnosis. Conclusions We identifiedGNPTAB mutations in all patients with ML II/III, but did not identify a hot spot in Korean patients. We successfully performed prenatal diagnosis using molecular investigation.